Digital Marketing Training and Mentoring in Entrepreneurship for Teenagers of The Pik-R Genre in Surakarta's Type Village - RAHADHINI, Marjam Desma; ZAKIYAH, Nadiya Fikriyatuz; SAPUTRI, Elysa Cristiana (PT Keberlanjutan Strategis Indonesia, 2025)
Many opportunities in digital business have not been maximized by young people, which is due to various reasons, including the lack of understanding of business actors regarding information technology, creativity and business innovation, as well as management in digital business and strategy. Through digital marketing training, young people are expected to be able to open business opportunities independently and sustainably, namely by becoming entrepreneurs. Digital marketing is an important tool used by various sectors, including micro, small, and medium enterprises (MSMEs), to expand market reach and increase competitiveness. Increasing digital marketing literacy is also the task of the university as a form of community service in order to foster interest in entrepreneurship by collaborating with the DP3AP2KB Office of Surakarta City through the GenRe (Generation Planned) Forum. In accordance with the purpose of GenRe (Generation Planned), which is to serve as a forum for accelerating action to create productive youth by instilling life skills. PIK-R Tipes Village, Serengan District, Surakarta City, as a forum for youth at the village level, has 50 active youth members aged between 15-25 years. The youth of PIK-R Tipes Village are considered active and have an interest in entrepreneurship. The Creative Economy (Ekraf) program at PIK-R Tipes Village includes herbal medicine (jamu), wedang uwuh (a traditional drink), and fish and vegetable cultivation, among other products. Therefore, digital marketing is needed to increase the product's awareness and sales turnover.